POWERFUL PRINCESSES : 10 UNTOLD STORIES OF HISTORY'S BOLDEST HEROINES - Buckingham, Angela; Gilbert, Yvonne ([Fitzroy, Victoria] : Five Mile, 2022)
A princess story collection like no other... These princess stories are not fairytales for small children. They are true tales of real women that every young person should know. These fast paced, action packed tales are stories that have been lost, stories that have remained untold. They come from every corner of the world and across history, but the single thing they share is that each is, in their own way, a powerful princess. These princesses are: Deep minded; Courageous; Warring; Healing; Mighty; Artful; Rebellious; Wise; Sage; Stoic. Discover the true tales of history's boldest heroines.
Keywords: Princesses -- Juvenile literature; Women heroes -- Juvenile literature; Picture books; Alphabet books